Melioidosis in Malaysia - Puthucheary, Savithri Devi (Malaysian Medical Association, 2009)
Melioidosis is an important cause of sepsis in the tropics, is caused by an environmental saprophyte--B. pseudomallei. It affects mainly adults with underlying predisposing condition such as diabetes. The range of symptoms varies from benign and localized abscesses, to severe community-acquired pneumonia to acute fulminating septicaemia with multiple abscesses often leading to death. B. pseudomallei is an intracellular pathogen and some of the virulence mechanisms that govern the complex interaction between the organism and the host have been elucidated. Isolation of B. pseudomallei from bodily fluids of patients remains the "gold standard" in diagnosis but a sensitive and specific serological test can lend support to the diagnosis of melioidosis. Ceftazidime is the treatment of choice for severe melioidosis, but the response is slow. Maintenance or eradication therapy for a prolonged period is necessary to prevent relapse and recurrence. Monitoring IgG antibody levels may be useful as a guideline to determine the duration of eradication therapy.